Dispersion liquid, conductive film and manufacturing method thereof, electrode, and solar cell
A dispersion liquid comprising a carbon material, an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound improves wettability and adhesion, resulting in a conductive film with enhanced conductivity and catalytic activity for solar cells.
Patent Information
- Application Number
- JP2020569534
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-01
- Filing Date
- 2020-01-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-01-21
AI Technical Summary
Conventional dispersion liquids for carbon nanotubes (CNTs) suffer from insufficient wettability and adhesion to substrates, leading to inadequate performance in conductive films, particularly in applications like dye-sensitized solar cells, where high conductivity and catalytic activity are required.
A dispersion liquid containing a carbon material, a condensate of an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound, along with a solvent, improves wettability and adhesion by enhancing dispersibility and film strength, resulting in a conductive film with high conductivity and catalytic activity.
The solution enables the formation of a conductive film with excellent adhesion to substrates, leading to improved conductivity, film strength, and catalytic activity, thereby enhancing the conversion efficiency of solar cells.
Smart Images

Figure 0007604895000006 
Figure 0007604895000001 
Figure 0007604895000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a dispersion, a conductive film and a manufacturing method thereof, an electrode, and a solar cell, and in particular to a dispersion, a conductive film obtained using the dispersion and a manufacturing method thereof, an electrode including the conductive film, and a solar cell including the electrode. [Background technology]
[0002] Carbon nanotubes (hereinafter sometimes referred to as "CNTs"), a type of carbon material, have various excellent properties such as electrical conductivity, thermal conductivity, and mechanical strength, and various industrial applications have been considered for some time. For example, focusing on the excellent electrical conductivity, technology to form conductive films with CNTs has been considered for some time.
[0003] A conductive film containing CNTs can be formed on a substrate by, for example, applying a carbon nanotube dispersion (hereinafter sometimes referred to as a "CNT dispersion") containing CNTs, a solvent, and a dispersant onto the substrate and drying it. In order to improve the performance of such conductive films and conductive films having a conductive film on a substrate, attempts have been made to improve the dispersant and CNT dispersion used.
[0004] For example, Patent Document 1 reports that a transparent conductive film having a conductive film made of CNTs and an aromatic polymer as a dispersant, and a layer made of a resin layer on the conductive film, and having a specific light transmittance and surface resistivity, is highly durable, highly conductive, and has excellent light transmittance.
[0005] Furthermore, for example, Patent Document 2 reports that an aqueous CNT dispersion containing a dispersant such as a polysaccharide having a number average molecular weight of 10,000 or more and 150,000 or less at a specific ratio relative to the CNTs and having a pH adjusted within a specific range, maintains high dispersibility while exhibiting excellent stability against high shear forces.
[0006] For example, Patent Document 3 reports that polystyrene sulfonate copolymers containing styrene sulfonate monomer residues, maleimide residues having a substituted or unsubstituted aromatic hydrocarbon group on the nitrogen atom, and other vinyl monomer residues derived from itaconic acid, fumaric acid, and the like as repeating structural units, each of which is represented by a specific structural formula, and in which the respective residue contents are 30 to 95 mol %, 5 to 70 mol %, and 0 to 20 mol %, respectively, have a high ability to disperse CNTs and the like in an aqueous medium.
[0007] Furthermore, for example, Patent Document 4 reports that when dispersing CNTs in a solvent, the use of a polymer dispersant made of a polymer containing sulfonic acid group-containing monomer units and containing ethylenically unsaturated aliphatic carboxylic acid monomer units in a specific ratio as a dispersant makes it possible to suppress aggregation of CNTs in the CNT dispersion while improving the adhesion between the conductive film formed using the dispersion and the substrate. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2009-163959 A [Patent Document 2] JP 2013-199419 A [Patent Document 3] International Publication No. 2013 / 042482 [Patent Document 4] International Publication No. 2015 / 115102 Summary of the Invention [Problem to be solved by the invention]
[0009] Here, a dispersion such as a CNT dispersion is required to have coatability (wettability) with respect to a substrate. A conductive film formed from the dispersion is required to have excellent electrical conductivity and adhesion to the substrate. Furthermore, for example, when the conductive film is used as a counter electrode of a dye-sensitized solar cell, excellent catalytic activity is required. A solar cell manufactured using the conductive film is required to have high conversion efficiency.
[0010] However, in the above conventional techniques, the coating property (wettability) of the dispersion to the substrate and / or the adhesion between the conductive film formed from the dispersion and the substrate are still insufficient. Therefore, the above conventional techniques have room for improvement in terms of improving the coating property (wettability) of the dispersion to the substrate and improving the adhesion between the conductive film formed from the dispersion and the substrate.
[0011] Therefore, the present invention aims to provide a dispersion liquid capable of improving the coatability (wettability) to a substrate and forming a conductive film having high adhesion to the substrate. The present invention also aims to provide the conductive film, an electrode including the conductive film, and a solar cell including the electrode. [Means for solving the problem]
[0012] The present inventors have conducted extensive research to achieve the above object, and have found that a dispersion containing a carbon material (A), a condensate (B) of an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound, and a solvent (C) can improve the coatability (wettability) to a substrate and form a conductive film having high adhesion to the substrate, thereby completing the present invention.
[0013] That is, the present invention aims to advantageously solve the above problems, and the dispersion of the present invention is characterized by containing a carbon material (A), a condensate (B) of an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound, and a solvent (C). In this way, by containing the carbon material (A), the condensate (B) of an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound, and the solvent (C), it is possible to improve the coatability (wettability) to the substrate, and to form a conductive film that has high adhesion to the substrate. In this specification, "aromatic sulfonic acid compound" means "a compound in which any of the hydrogen atoms in an aromatic compound is substituted with -SO3X (X is a hydrogen atom or a cation)," and "hydroxyphenol compound" means "a compound having one or more hydroxy groups (hydroxyl groups)" other than "aromatic sulfonic acid compound."
[0014] Here, in the dispersion of the present invention, the molar ratio of the hydroxyphenol compound monomer units derived from the hydroxyphenol compound to the aromatic sulfonic acid compound monomer units derived from the aromatic sulfonic acid compound in the condensate (B) (hydroxyphenol compound monomer units / aromatic sulfonic acid compound monomer units) is preferably 1 / 9 or more and 9 / 1 or less. If the molar ratio of the aromatic sulfonic acid compound monomer units to the hydroxyphenol compound monomer units in the condensate (B) is within a predetermined range, the dispersibility of the condensate (B) can be improved, and a conductive film having high adhesion to a substrate can be efficiently formed.
[0015] In the dispersion of the present invention, the weight average molecular weight (standard polyethylene glycol equivalent) of the condensate (B) is preferably 500 or more and 100,000 or less. If the weight average molecular weight (standard polyethylene glycol equivalent) of the condensate (B) is 500 or more and 100,000 or less, the dispersibility of the carbon material can be improved, and the coating property (wettability) to the substrate can be improved. As a result, a conductive film having high adhesion to the substrate can be efficiently formed, and a conductive film having improved conductivity, film strength, and catalytic activity when used as an electrode can be obtained. In addition, a solar cell manufactured using this conductive film can obtain high conversion efficiency.
[0016] Furthermore, in the dispersion of the present invention, the condensate (B) is preferably a resol type.
[0017] In the dispersion of the present invention, the condensate (B) is preferably represented by the following general formula (1) or the following general formula (2). [ka] [In the general formula (1) and the general formula (2), X is a hydrogen atom or a cation, R1 is a hydroxyl group, -CH2-OH 、 Or a group represented by the following general formula (3), in which m, n, o and p are each an integer of 1 or more. [ka] [In general formula (3), l is an integer of 0 to 4, Q is a divalent organic group, and R is a hydroxyl group, -CH-OH, or a hydrogen atom.]
[0018] Furthermore, in the dispersion of the present invention, Q in the general formula (3) is preferably a sulfonyl group.
[0019] In the dispersion of the present invention, the carbon material (A) is preferably a fibrous carbon nanostructure.
[0020] Furthermore, in the dispersion of the present invention, it is preferable that the solvent (C) contains water and the pH of the dispersion is less than 7.
[0021] The dispersion of the present invention preferably contains 50 parts by mass or more and 500 parts by mass or less of the condensate (B) per 100 parts by mass of the carbon material (A).
[0022] The present invention also aims to advantageously solve the above problems, and the conductive film of the present invention is characterized in that it is obtained by using any one of the dispersions described above. By using the dispersion of the present invention, a conductive film having excellent adhesion to a substrate can be provided.
[0023] The present invention also aims to advantageously solve the above problems, and provides an electrode comprising the conductive film described above. The electrode comprising the conductive film of the present invention has excellent conductivity.
[0024] The present invention also aims to advantageously solve the above problems, and provides a solar cell comprising the electrode described above. A solar cell comprising the electrode of the present invention has high conversion efficiency.
[0025] The present invention also aims to advantageously solve the above problems, and the method for producing a conductive film of the present invention is characterized by comprising the steps of: (1) applying any one of the above-mentioned dispersions onto a substrate and drying to form a conductive film; and (2) washing the conductive film obtained in the step (1) with a solvent to remove at least a part of the condensate (B) from the conductive film. The method for producing a conductive film of the present invention can efficiently produce a conductive film having excellent adhesion to a substrate. Effect of the Invention
[0026] According to the present invention, it is possible to provide a dispersion liquid capable of improving the coatability (wettability) to a substrate and forming a conductive film having high adhesion to the substrate. Furthermore, according to the present invention, it is possible to provide a conductive film having high adhesion to a substrate and a method for producing the same, an electrode including the conductive film and having high conductivity, and a solar cell including the electrode and having high conversion efficiency. [Brief description of the drawings]
[0027]
Figure 1
[0028] (dispersion) The carbon material dispersion of the present invention contains a carbon material (A), a condensate (B), and a solvent (C), and may further contain any other components as necessary. The dispersion of the present invention is preferably acidic. When the dispersion is acidic, when the dispersion is applied onto a conductive layer formed on a substrate, the dispersion can improve adhesion between the conductive layer formed on the substrate and the conductive layer formed by the dispersion due to corrosion of the conductive layer formed on the substrate.
[0029] <Carbon material (A)> The carbon material (A) is not particularly limited, and examples of the carbon material that can be used include conductive fibrous carbon nanostructures, graphene, fullerene, carbon nanohorns, graphite, activated carbon, carbon fibers, porous carbon, expanded graphite, carbon particles (e.g., carbon black such as Ketjen Black and acetylene black), etc. These may be used alone or in combination of two or more. Among these, fibrous carbon nanostructures are preferred because the conductive film obtained has excellent strength and catalytic performance.
[0030] <<Fibrous carbon nanostructures>> Specific examples of fibrous carbon nanostructures that can be used include structures formed by stacking cone-shaped structures such as cup-stacked carbon nanotubes, cylindrical carbon nanostructures such as carbon nanobatts and carbon nanotubes (CNTs), and non-cylindrical carbon nanostructures such as graphene nanoribbons in which a carbon hexagonal ring network is formed into a flattened cylinder. These may be used alone or in combination of two or more.
[0031] Among the above, it is more preferable to use a fibrous carbon nanostructure containing CNT as the fibrous carbon nanostructure. The fibrous carbon nanostructure may be composed of only CNT. If a fibrous carbon nanostructure containing CNT is used, even if the amount of the fibrous carbon nanostructure is small, it is possible to efficiently impart properties such as electrical conductivity, film strength, and catalytic activity when used in solar cell electrodes to the obtained conductive film.
[0032] As the CNT in the fibrous carbon nanostructure, single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used without any particular limitation. The CNT is preferably a single-walled to five-walled carbon nanotube, more preferably a single-walled carbon nanotube. These may be used alone or in combination of two or more. The fewer the number of walls of the carbon nanotube, the larger the specific surface area becomes even with a small amount of blending, and the obtained conductive film can be provided with favorable properties such as catalytic activity when used in a solar cell electrode.
[0033] In addition, the average diameter of the fibrous carbon nanostructure is preferably 1 nm or more, preferably 60 nm or less, more preferably 30 nm or less, and particularly preferably 10 nm or less. If the average diameter of the fibrous carbon nanostructure is 1 nm or more, the dispersibility of the fibrous carbon nanostructure can be improved, and properties such as electrical conductivity can be stably and satisfactorily imparted to the conductive film. In addition, if the average diameter of the fibrous carbon nanostructure is 60 nm or less, even with a small blending amount, properties such as catalytic activity can be efficiently imparted to the obtained conductive film when used in a solar cell electrode. In the present invention, the "average diameter of fibrous carbon nanostructures" can be determined by measuring the diameter (outer diameter) of, for example, 20 fibrous carbon nanostructures on a transmission electron microscope (TEM) image and calculating the number average value.
[0034] As the fibrous carbon nanostructure, it is preferable to use a fibrous carbon nanostructure having a ratio (3σ / Av) of the value (3σ) obtained by multiplying the standard deviation of the diameter (σ: sample standard deviation) by 3 to the average diameter (Av) of more than 0.20 and less than 0.60, more preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.25, and particularly preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.40. By using a fibrous carbon nanostructure having a 3σ / Av of more than 0.20 and less than 0.60, the performance of the conductive film produced can be further improved. The average diameter (Av) and standard deviation (σ) of the fibrous carbon nanostructures may be adjusted by changing the manufacturing method or manufacturing conditions of the fibrous carbon nanostructures, or by combining multiple types of fibrous carbon nanostructures obtained by different manufacturing methods.
[0035] The fibrous carbon nanostructures that are usually used are those that show a normal distribution when the diameter measured as described above is plotted on the horizontal axis and the frequency on the vertical axis and approximated with a Gaussian.
[0036] In addition, the average length of the fibrous carbon nanostructure is preferably 10 μm or more, more preferably 50 μm or more, particularly preferably 80 μm or more, and preferably 600 μm or less, more preferably 500 μm or less, particularly preferably 400 μm or less. If the average length is 10 μm or more, a conductive path can be formed in the conductive film with a small amount of compounding, and the strength of the conductive film is high. If the average length is 600 μm or less, the coatability to the substrate can be improved when applying the dispersion. Therefore, if the average length of the fibrous carbon nanostructure is within the above range, the surface resistivity of the conductive film can be sufficiently reduced and high catalytic activity can be imparted to the conductive film. In the present invention, the average length of the "fibrous carbon nanostructure" can be determined by measuring the lengths of, for example, 20 fibrous carbon nanostructures on a scanning electron microscope (SEM) image and calculating the number average value.
[0037] Furthermore, the fibrous carbon nanostructures usually have an aspect ratio of more than 10. The aspect ratio of the fibrous carbon nanostructures can be determined by measuring the diameter and length of 100 randomly selected fibrous carbon nanostructures using a scanning electron microscope or a transmission electron microscope and calculating the average value of the ratio of the diameter to the length (length / diameter).
[0038] In addition, the fibrous carbon nanostructure has a BET specific surface area of 200 m 2 / g or more, and 2 / g or more is more preferable, and 600m 2 / g or more is particularly preferable, and 2000m 2 / g or less, and 2 / g or less is more preferable, and 1600m 2 It is particularly preferable that the BET specific surface area of the fibrous carbon nanostructure is 200 m 2 / g or more, the dispersibility of the fibrous carbon nanostructure is increased, and even with a small blending amount, the conductive film obtained can be imparted with favorable properties such as conductivity and catalytic activity when used in solar cell electrodes. 2 / g or less, the obtained conductive film can be imparted with good properties such as electrical conductivity and catalytic activity when used in a solar cell electrode, and the coatability of the dispersion can be stabilized. In the present invention, the term "BET specific surface area" refers to a nitrogen adsorption specific surface area measured by the BET method.
[0039] In addition, it is preferable that the t-plot obtained from the adsorption isotherm of the fibrous carbon nanostructure shows an upwardly convex shape. The "t-plot" can be obtained by converting the relative pressure into the average thickness t (nm) of the nitrogen gas adsorption layer in the adsorption isotherm of the fibrous carbon nanostructure measured by the nitrogen gas adsorption method. That is, the t-plot of the fibrous carbon nanostructure can be obtained by determining the average thickness t of the nitrogen gas adsorption layer corresponding to the relative pressure from a known standard isotherm in which the average thickness t of the nitrogen gas adsorption layer is plotted against the relative pressure P / P0, and performing the above conversion (t-plot method by de Boer et al.).
[0040] Here, in a material having pores on the surface, the growth of a nitrogen gas adsorption layer is classified into the following processes (1) to (3). The slope of the t-plot changes depending on the processes (1) to (3) below. (1) The process of forming a monolayer of nitrogen molecules on the entire surface (2) Formation of multilayer adsorption and the associated capillary condensation filling process in the pores (3) The formation of multilayer adsorption on an apparently non-porous surface whose pores are filled with nitrogen
[0041] In the t-plot showing an upward convex shape, the plot is located on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, whereas as t increases, the plot shifts downward from the straight line. Fibrous carbon nanostructures having such a t-plot shape have a large ratio of the internal specific surface area to the total specific surface area of the fibrous carbon nanostructure, indicating that a large number of openings are formed in the carbon nanostructures that make up the fibrous carbon nanostructure.
[0042] The inflection point of the t-plot of the fibrous carbon nanostructure is preferably in a range satisfying 0.2≦t(nm)≦1.5, more preferably in a range of 0.45≦t(nm)≦1.5, and particularly preferably in a range of 0.55≦t(nm)≦1.0. If the inflection point of the t-plot of the fibrous carbon nanostructure is within this range, the dispersibility of the fibrous carbon nanostructure can be increased, and the properties such as the conductivity of the conductive film can be improved with a small blending amount. Specifically, if the inflection point value is less than 0.2, the fibrous carbon nanostructure is likely to aggregate and the dispersibility is reduced, and if the inflection point value is more than 1.5, the fibrous carbon nanostructures are likely to be entangled with each other, and the dispersibility may be reduced. The "position of the bending point" is the intersection of the approximation line A in the above-mentioned process (1) and the approximation line B in the above-mentioned process (3).
[0043] Furthermore, the fibrous carbon nanostructure preferably has a ratio (S2 / S1) of the internal specific surface area S2 to the total specific surface area S1 obtained from a t-plot of 0.05 to 0.30. If the value of S2 / S1 of the fibrous carbon nanostructure is within this range, the dispersibility of the fibrous carbon nanostructure can be increased, and the properties such as the conductivity of the conductive film can be improved with a small blend amount. Here, the total specific surface area S1 and the internal specific surface area S2 of the fibrous carbon nanostructure can be obtained from the t-plot. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximation line in step (1), and the external specific surface area S3 can be obtained from the slope of the approximation line in step (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.
[0044] Incidentally, the measurement of the adsorption isotherm of the fibrous carbon nanostructure, the creation of t-plots, and the calculation of the total specific surface area S1 and the internal specific surface area S2 based on the analysis of the t-plots can be performed, for example, using a commercially available measuring device, "BELSORP (registered trademark)-mini" (manufactured by BEL Japan Co., Ltd.).
[0045] Furthermore, the fibrous carbon nanostructure containing CNTs suitable for the fibrous carbon nanostructure preferably has a radial breathing mode (RBM) peak when evaluated by Raman spectroscopy. Note that the Raman spectrum of a fibrous carbon nanostructure consisting only of multi-walled carbon nanotubes having three or more walls does not have an RBM.
[0046] Furthermore, the fibrous carbon nanostructure containing CNTs preferably has a ratio of G band peak intensity to D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 to 10.0, more preferably 1.0 to 5.0. If the G / D ratio is 0.5 to 10.0, the resulting conductive film can be provided with favorable properties such as catalytic activity when used in a solar cell electrode.
[0047] Furthermore, in the fibrous carbon nanostructure containing CNT, the amount of oxygen atoms is preferably 5 atomic % or less, more preferably 2 atomic % or less, and particularly preferably 1 atomic % or less, based on the total amount of carbon atoms and oxygen atoms, as determined by elemental analysis using XPS. If the amount of oxygen atoms is within the preferred range, the resulting conductive film can be provided with favorable properties such as catalytic activity when used in a solar cell electrode.
[0048] In the fibrous carbon nanostructure containing CNT, the proportion of carbon atoms, as determined by elemental analysis of CHN, is preferably 85% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more, and the proportion of hydrogen atoms is preferably 1% by mass or less, more preferably 0.8% by mass or less, more preferably 0.3% by mass or less, and particularly preferably 0.1% by mass or less. If the ratio of carbon atoms (hydrogen atoms) is within the preferred range, the obtained conductive film can be imparted with favorable properties such as catalytic activity when used in a solar cell electrode.
[0049] In addition, the fibrous carbon nanostructure containing CNT can be produced by using a known synthesis method of CNT, such as an arc discharge method, a laser ablation method, a chemical vapor deposition method (CVD method), etc., without any particular limitation. Specifically, the fibrous carbon nanostructure containing CNT can be efficiently produced in accordance with a method (super growth method; see International Publication No. 2006 / 011655) in which, for example, a raw material compound and a carrier gas are supplied onto a substrate having a catalyst layer for producing carbon nanotubes on its surface, and when CNT is synthesized by a chemical vapor deposition method (CVD method), a trace amount of an oxidizing agent (catalyst activation material) is made to exist in the system, dramatically improving the catalytic activity of the catalyst layer. In the following, the carbon nanotube obtained by the super growth method may be referred to as "SGCNT". Furthermore, the fibrous carbon nanostructure produced by the super-growth method may be composed only of SGCNTs, or may contain, in addition to SGCNTs, other carbon nanostructures, such as non-cylindrical carbon nanostructures.
[0050] The content of the carbon material (A) in the dispersion is not particularly limited, but is preferably 0.001 mass% or more, more preferably 0.01 mass% or more, and particularly preferably 0.1 mass% or more, of the total dispersion, and is preferably 30.0 mass% or less, more preferably 10.0 mass% or less, even more preferably 5.0 mass% or less, and particularly preferably 1.0 mass% or less.
[0051] <Condensation product (B)> The condensate (B) is a condensate of an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound, and functions as a dispersant for the carbon material (A). The condensate (B) has excellent dispersibility for the carbon material (A) such as CNT, and is easily removed by washing with a solvent, so that a conductive film having improved catalytic activity, high adhesion, and high strength of the film itself can be obtained, and thus a good electrode such as a counter electrode can be obtained.
[0052] <<Aromatic sulfonic acid compounds>> The term "aromatic sulfonic acid compound" means "a compound in which any of the hydrogen atoms in an aromatic compound is replaced with -SO3X (X is a hydrogen atom or a cation)." Examples of aromatic sulfonic acid compounds include phenolsulfonic acids (PSA) such as p-phenolsulfonic acid, o-phenolsulfonic acid, and phenoldisulfonic acid; naphtholsulfonic acids such as 1-naphthol-4-sulfonic acid, 2-naphthol-6-sulfonic acid, 2-naphthol-7-sulfonic acid, 1-naphthol-6-sulfonic acid, and 2-naphthol-8-sulfonic acid; naphthalenesulfonic acids such as 4-aminonaphthalenesulfonic acid; sulfanilic acid (4-aminobenzenesulfonic acid); etc. These may be used alone or in combination of two or more at any ratio. Among these, phenolsulfonic acid (PSA) and 4-aminobenzenesulfonic acid are preferred in terms of condensation reactivity and the solubility of the resulting condensation product in a solvent.
[0053] <<Hydroxyphenol compounds>> The term "hydroxyphenol compound" refers to a compound having one or more hydroxy groups (hydroxyl groups) other than an aromatic sulfonic acid compound. Examples of hydroxyphenol compounds include hydroxyphenols such as bisphenol A, 4,4-biphenol, 3,3,5,5-tetramethyl-4,4-biphenol, and bis(4-hydroxy-3,5-dimethylphenyl)methane; those having a naphthalene skeleton such as 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, and 1,1-bis(2-naphthol); hydroxydiphenylsulfones (BS) such as 4,4'-dihydroxydiphenylsulfone, 2,4'-dihydroxydiphenylsulfone, and bis(4-hydroxy-3,5-dimethylphenyl)sulfone; and polyfunctional phenols such as 1,1,1-tris(4-hydroxyphenyl)methane and 1,1,2,2,-tetrakis(4-hydroxyphenyl)ethane. These may be used alone or in combination of two or more in any ratio. Among these, in terms of ease of production, adhesion to a substrate, and solubility of the resulting condensation product in a solvent, a compound having 2 to 4 hydroxyl groups, 1 to 3 six-membered rings, and a linking group such as a sulfonyl group, such as dihydroxydiphenylsulfone, is preferred.
[0054] <<Aldehyde compounds>> Examples of the aldehyde compound include aliphatic aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, and glyoxal; and aldehydes having a cyclic structure such as furfural, benzaldehyde, salicylaldehyde, and paraformaldehyde. The aldehyde compound may be used in the form of an aqueous solution. The aldehyde compound is preferably used in an amount of about 0.5 to 2 times by mole, more preferably about 1.0 to 1.9 times by mole, based on the total amount of the aromatic sulfonic acid compound and the hydroxyphenol compound used. If the amount is more than the lower limit, it is possible to prevent a large amount of unreacted aromatic sulfonic acid compound and hydroxyphenol compound from remaining at the end of the reaction, and if the amount is less than the upper limit, it is possible to prevent a large amount of free aldehyde compound in the condensation product liquid.
[0055] The condensation reaction of the aromatic sulfonic acid compound, the hydroxyphenol compound and the aldehyde compound is carried out by a known method. For example, an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound are subjected to a condensation reaction in the presence of an acid catalyst or an alkali catalyst to produce an aldehyde condensate (condensate (B)). When the aromatic sulfonic acid compound, the hydroxyphenol compound and the aldehyde compound are subjected to a condensation reaction, water, an alcohol or the like is used as a solvent.
[0056] Examples of the acid catalyst include hydrochloric acid, sulfuric acid, oxalic acid, acetic acid, toluenesulfonic acid, etc. These may be used alone or in combination of two or more kinds in any ratio. Examples of the alkali catalyst include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkaline earth metal hydroxides such as calcium hydroxide and barium hydroxide; amines such as ammonia and triethylamine; and the like. These may be used alone or in combination of two or more at any ratio. Among these, sodium hydroxide is preferred from the viewpoint of ease of operation. As for the structure of the condensate (B) described later, when a novolak type is prepared, an acid catalyst is preferably selected, and when a resol type is prepared, an alkali catalyst is preferably selected. When an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound are subjected to a condensation reaction in the presence of an alkali catalyst, an amount of alkali necessary for neutralizing the strongly acidic components present in the reaction system, such as free sulfuric acid and sulfonic acid groups bonded to phenols, is used.
[0057] In preparing the condensate (B), the reaction temperature and reaction time are not particularly limited, and may be appropriately selected so that the production of the condensate (B) having a desired weight average molecular weight (in terms of standard polyethylene glycol) can be easily controlled.
[0058] The reaction temperature is not particularly limited, but is preferably 60° C. or higher and 120° C. or lower. The reaction time is not particularly limited, but is preferably 3 hours or more and 20 hours or less. The resulting formaldehyde condensate may be isolated after the condensation reaction, or the reaction product may be used as it is.
[0059] The structure of the condensate (B) may be, for example, a novolac type (thermoplastic type) such as random novolac or high-ortho novolac, or a resole type (thermosetting type) such as benzyl ether resole, ammonia resole, or alkali resole. From the viewpoint of adhesion between the carbon material (A) such as CNT and the substrate after the dispersion is applied and dried, the structure of the condensate (B) is preferably a resole type, and more preferably represented by the following general formula (1) or the following general formula (2). [ka] [In general formula (1) and general formula (2), X is a hydrogen atom or a cation, R1 is a hydroxyl group, -CH2-OH, or a group represented by the following general formula (3), and m, n, o, and p are each an integer of 1 or more, preferably an integer of 1≦m≦235, an integer of 1≦n≦206, an integer of 1≦o≦192, or an integer of 1≦p≦206.] [ka] [In general formula (3), l is an integer of 0 to 4; Q is a divalent organic group (e.g., -CH2-, -C(CH3)2-, -S-, -SO2- (sulfonyl group), -NH-, -N=N-), preferably -S-, -SO2- (sulfonyl group), more preferably -SO2- (sulfonyl group); and R2 is a hydroxyl group, -CH2-OH, or a hydrogen atom.]
[0060] Examples of the cation represented by X in the general formula (1) include a lithium ion, a sodium ion, a potassium ion, a calcium ion, a magnesium ion, and an ammonium ion.
[0061] In the condensate (B), the molar ratio of the hydroxyphenol compound monomer units derived from the hydroxyphenol compound to the aromatic sulfonic acid compound monomer units derived from the aromatic sulfonic acid compound (hydroxyphenol compound monomer units / aromatic sulfonic acid compound monomer units) is preferably 1 / 9 or more, more preferably 1 / 5 or more, even more preferably 1 / 4 or more, and particularly preferably 1 / 3 or more, and is preferably 9 / 1 or less, more preferably 5 / 1 or less, even more preferably 4 / 1 or less, and particularly preferably 3 / 1 or less. When the molar ratio is equal to or more than the lower limit, the solubility of the condensate (B) in the solvent (C) can be improved to form a conductive film having high adhesion to a substrate, and when the molar ratio is equal to or less than the upper limit, the dispersibility of the carbon material (A) can be improved.
[0062] The weight average molecular weight (in terms of standard polyethylene glycol) of the condensate (B) is preferably 500 or more, more preferably 1,000 or more, even more preferably 2,000 or more, and particularly preferably 5,000 or more, and is preferably 100,000 or less, more preferably 50,000 or less, and particularly preferably 30,000 or less. When the weight-average molecular weight (in terms of standard polyethylene glycol) of the condensate (B) is at least the above-mentioned lower limit, the obtained conductive film can be imparted with sufficient adhesion to the substrate and sufficient film strength, whereas when the weight-average molecular weight is not more than the above-mentioned upper limit, the dispersibility of the carbon material, the rinsability of the obtained conductive film, and the electrode performance of the obtained electrode are excellent.
[0063] The content of the condensate (B) per 100 parts by mass of the carbon material (A) is preferably 50 parts by mass or more, more preferably 80 parts by mass or more, and particularly preferably 130 parts by mass or more, and is preferably 500 parts by mass or less, more preferably 350 parts by mass or less, and particularly preferably 250 parts by mass or less. When the content is equal to or more than the above lower limit, the obtained conductive film can be imparted with sufficient adhesion to the substrate and sufficient film strength, and when the content is equal to or less than the above upper limit, the dispersibility and rinsability of the carbon material, and the electrode performance of the obtained electrode are excellent.
[0064] <Solvent (C)> The solvent (C) may be either aqueous or organic, but it is preferable to use an aqueous solvent (i.e., it is preferable that the solvent (C) contains water). The aqueous solvent is not particularly limited as long as the carbon material (A) such as CNT can be dispersed therein, and water may be used alone or a mixed solvent of solvents miscible with water may be used. Examples of solvents that are miscible with water include ethers (dioxane, tetrahydrofuran, methyl cellosolve, ethylene glycol dimethyl ether, ethylene glycol butyl ether, etc.), ether alcohols (ethoxyethanol, methoxyethoxyethanol, etc.), esters (methyl acetate, ethyl acetate, etc.), ketones (acetone, methyl isobutyl ketone, cyclohexanone, methyl ethyl ketone, etc.), alcohols (methanol, ethanol, isopropanol, propylene glycol, ethylene glycol, diacetone alcohol, phenol, etc.), lower carboxylic acids (acetic acid, etc.), amines (triethylamine, trimethanolamine, etc.), nitrogen-containing polar solvents (N,N-dimethylformamide, nitromethane, N-methylpyrrolidone, acetonitrile, etc.), sulfur compounds (dimethyl sulfoxide, etc.), etc. These may be used alone or in combination of two or more in any ratio. Among these, as the solvent miscible with water, ethers, ketones and alcohols are preferred from the viewpoint of improving the stability of the dispersion liquid. These may be degassed at appropriate times.
[0065] When the solvent (C) of the dispersion contains water, the pH of the dispersion is not particularly limited, but is preferably 0.1 or more, more preferably 0.2 or more, and particularly preferably 0.5 or more, and is preferably less than 7 (i.e., acidic), more preferably 6 or less, even more preferably 5 or less, even more preferably 4 or less, and particularly preferably 2.5 or less. By setting the pH of the dispersion within the above range, the stability of the dispersion can be ensured. In order to lower the pH of the dispersion, an acidic substance may be added, such as sulfuric acid, hydrochloric acid, nitric acid, citric acid, oxalic acid, tartaric acid, formic acid, phosphoric acid, etc., and from the viewpoint of ease of rinsing, hydrochloric acid and nitric acid are more preferable.
[0066] <Other ingredients> Other components include inorganic substances such as silica, metal particles, binders, conductive assistants, surfactants, defoamers, antioxidants, preservatives, etc. Known components may be used as appropriate. One type may be used alone, or two or more types may be used in combination at any ratio.
[0067] <Method of manufacturing dispersion liquid> The method for producing the dispersion is not particularly limited, but a solution containing the condensate (B) obtained by dissolving the condensate (B) functioning as a dispersant in a solvent may be added to a mixture of the carbon material (A) and the solvent (C), or the carbon material (A) may be added to a mixture of the condensate (B) and the solvent (C). In addition, an alkaline aqueous solution containing the condensate (B) obtained by dissolving the condensate (B) functioning as a dispersant in a good solvent (e.g., an alkaline aqueous solution) may be added to a mixture of the carbon material (A) and the solvent (C) (e.g., an acidic aqueous solution).
[0068] The mixing and dispersing treatment of the dispersion liquid can be carried out by using a known method. For example, a wet jet mill such as a Nanomizer or Ultimizer, a high-pressure homogenizer, an ultrasonic disperser, a ball mill, a sand grinder, a Dyno Mill, a spike mill, a DCP mill, a basket mill, a paint conditioner, a high-speed stirring device such as a homomixer, etc. can be used. These may be used alone or in combination of two or more. The production efficiency of the dispersion can be improved by using high-speed stirring equipment such as a high-pressure homogenizer, ultrasonic disperser, ball mill, sand grinder, Dyno Mill, spike mill, DCP mill, basket mill, paint conditioner, or homomixer for preliminary dispersion, and using a wet jet mill such as a Nanomizer or Ultimizer, or a high-pressure homogenizer for main dispersion. The temperature during dispersion is not particularly limited, but is usually equal to or lower than the boiling point of the solvent, preferably equal to or lower than 60° C., more preferably equal to or lower than 40° C., and preferably equal to or higher than −10° C., more preferably equal to or higher than 0° C. Within this range, the solubility and structure of the dispersant can be controlled, the dispersibility of the carbon material (A) can be improved, and deterioration of the carbon material (A) can be suppressed even when it is treated in an acidic solution, for example.
[0069] (Conductive film) The conductive film of the present invention is formed using the above-mentioned dispersion. The conductive film of the present invention contains a well-dispersed carbon material (A), and therefore has excellent electrical conductivity and mechanical properties. Such a conductive film has excellent adhesion (adhesion) to the substrate and catalytic activity. The conductive film of the present invention is preferably used, for example, as a conductive film of a photoelectrode substrate or a counter electrode (catalytic electrode) substrate described later, or as a catalytic layer of a counter electrode (catalytic electrode). In particular, it is preferably used as a catalytic layer of a counter electrode (catalytic electrode).
[0070] (Method of manufacturing conductive film) The method for producing a conductive film of the present invention includes a step (1) of applying the dispersion of the present invention onto a substrate and drying the dispersion to form a conductive film, and a step (2) of washing the conductive film obtained in the step (1) with a solvent to remove at least a part of the condensate (B) from the conductive film, and further includes a step (3) of decomposing a part of the condensate (B) contained in the conductive film, as necessary.
[0071] <Process (1)> In step (1), the dispersion of the present invention is applied onto a substrate, and the applied dispersion is dried to form a conductive film.
[0072] <<Base material>> The substrate can be coated with the above-mentioned dispersion, and as long as it can support the resulting conductive film, there are no particular limitations on its shape, constituent material, and size (thickness, etc.), and they can be appropriately selected depending on the intended use. As the substrate, a substrate on which a known conductive film other than the conductive film of the present invention is formed, a substrate having an undercoat layer of a resin or the like, or a substrate having an organic / inorganic barrier layer having a barrier property against oxygen and moisture may be used.
[0073] As a method for applying the dispersion of the present invention onto a substrate, a known application method can be adopted. Examples of the method include dipping, roll coating, gravure coating, knife coating, air knife coating, roll knife coating, die coating, screen printing, spray coating, gravure offset, inkjet, spraying, etc. Among these, screen printing is preferred because it is easy to form an electrode pattern. Moreover, the coating may be carried out not only once but also several times as necessary, and two different coating methods may be combined. The coating thickness (wet thickness) when the dispersion of the present invention is applied onto a substrate is not particularly limited as long as the electrical conductivity of the resulting film is ensured, but is preferably 0.001 μm or more, more preferably 0.005 μm or more, and particularly preferably 0.01 μm or more, and is preferably 50 μm or less, more preferably 10 μm or less, and particularly preferably 3 μm or less. In addition, when the dispersion of the present invention is applied to a substrate, the amount of CNTs applied per unit area of the substrate is 0.001 mg / m 2 It is preferable that the concentration is 0.005 mg / m or more. 2 More preferably, it is 0.01 mg / m or more. 2 It is particularly preferable that the content is 50 g / m or more. 2 It is preferable that the thickness is less than 10 g / m 2 More preferably, it is 3 g / m or less. 2 It is particularly preferred that: In forming the conductive film of the present invention, the type (shape) and thickness of the carbon material used are usually reflected in the conductive film obtained. Therefore, the thickness of the conductive film of the present invention is not particularly limited, but is usually 100 nm to 1 mm. For example, when used as a counter electrode for organic solar cells such as dye-sensitized solar cells, organic thin-film solar cells, and perovskite solar cells, the thickness of the conductive film is usually 0.01 μm to 100 μm, preferably 0.1 μm to 20 μm, and more preferably 0.5 μm to 10 μm. Within this range, the conductive film has excellent conductivity and catalytic performance as an electrode, and when used as a module, has an excellent balance of the overall series resistance, etc. When the thickness of the conductive film is within the above range, the conductive film has excellent conductivity. Furthermore, the conductive film of the present invention has excellent conductivity. The sheet resistance of the conductive film of the present invention is usually 0.01 Ω / □ to 1000 Ω / □, preferably 0.1 Ω / □ to 100 Ω / □, and more preferably 0.5 to 20 Ω / □. The surface resistivity of this conductive film can be measured using a low resistivity meter (for example, product name "Loresta (registered trademark)-GP MCP-T610" manufactured by Mitsubishi Chemical Analytech Co., Ltd.) according to a method in accordance with JIS K7194.
[0074] Furthermore, as a method for drying the applied dispersion, a known drying method can be adopted. For example, the dispersion on the substrate is dried by a heating drying method such as air drying method or heat roll drying method, reduced pressure drying method, infrared irradiation method, light irradiation method using a xenon lamp or a flash lamp, or electromagnetic wave heating method using microwaves, etc., to form a conductive film on the substrate. The drying temperature is not particularly limited as long as it is possible to remove the solvent (C) by vaporization and is equal to or lower than the heat resistance temperature of the substrate. The drying temperature is preferably 0°C or higher, more preferably 15°C or higher, even more preferably room temperature or higher, particularly preferably 80°C or higher, preferably 250°C or lower, more preferably 200°C or lower, and particularly preferably 150°C or lower. The drying time is not particularly limited, but is preferably 0.1 minute or more and 150 minutes or less. The drying atmosphere is not particularly limited and may be a humidified atmosphere, air, an inert gas such as nitrogen or argon, or a reduced pressure such as vacuum.
[0075] In the method for producing a conductive film of the present invention, the following step (2) is carried out after step (1). From the viewpoint of more efficiently removing the condensate (B) (dispersant) from the conductive film, it is preferable to carry out both steps (2) and (3).
[0076] <Process (2)> In step (2), the conductive film obtained in step (1) is washed with a solvent to remove at least a portion of the condensate (B) (dispersant) from the conductive film. The washing may be performed, for example, on the conductive film obtained in step (1). In the washing, the conductive film is brought into contact with a solvent capable of dissolving the condensate (B) and the condensate (B) in the conductive film is dissolved in the solvent, thereby removing a part of the condensate (B) in the conductive film from the conductive film.
[0077] The solvent capable of dissolving the condensate (B) is not particularly limited, and the same solvent as the solvent (C) can be used. Among them, from the viewpoint of ease of handling, water, alcohols, ketones, nitrogen-containing polar solvents, etc. are preferred, and an alkaline aqueous solution is more preferred.
[0078] The conductive film can be washed using a solvent capable of dissolving the above-mentioned condensate (B) by, for example, immersing the conductive film in the solvent or applying the solvent to the conductive film. The conductive film may be washed multiple times. The washed conductive film can be dried using a known method. When the condensate (B) is removed by immersion in a solvent, the immersion time is preferably 30 seconds or more, more preferably 1 minute or more, particularly preferably 3 minutes or more, and preferably 1 hour or less, more preferably 30 minutes or less. If the immersion time is 30 seconds or more, the condensate (B) can be sufficiently removed. If the immersion time is 1 hour or less, it is possible to prevent the carbon material from falling off from the conductive film or the conductive film from peeling off from the substrate due to excessive washing.
[0079] <Process (3)> In step (3), at least one treatment selected from the group consisting of plasma treatment, UV treatment, and ozone treatment (hereinafter sometimes referred to as "decomposition treatment") is performed on the conductive film obtained in step (1) to decompose at least a portion of the condensate (B) contained in the conductive film. When both steps (2) and (3) are performed, the order of the steps is not particularly limited, but it is preferable to perform a decomposition treatment in step (3) on the conductive film that has been washed in step (2). That is, when both steps (2) and (3) are performed, it is preferable to decompose the condensate (B) remaining in the conductive film after washing in step (2) in step (3).
[0080] The decomposition treatment may be performed, for example, on a conductive film. In the decomposition treatment of the conductive film, at least one treatment selected from the group consisting of a plasma treatment, a UV treatment, and an ozone treatment is performed on the conductive film to decompose at least a part of the condensate (B) contained in the conductive film. The decomposition product generated during the decomposition treatment may be removed by a method such as washing after the decomposition treatment. From the viewpoint of ease of processing, it is preferable to use a UV treatment as the decomposition treatment.
[0081] Here, when the above-mentioned cleaning and / or decomposition treatment is performed, the amount of condensate (B) (dispersant) in the conductive film is reduced and the carbon content of the conductive film is increased; however, when long CNTs such as SGCNTs are used as the carbon material (A), the CNTs are entangled with each other to form a network structure, and therefore the layer shape can be well maintained even if the condensate (B) (dispersant) is removed.
[0082] The cleaning and decomposition treatment may be performed on a conductive film formed on a substrate, or on a conductive film peeled off from the substrate.
[0083] In the conductive film manufacturing method of the present invention, the content of the condensate (B) (dispersant) contained in the conductive film is reduced by carrying out the above-mentioned cleaning and / or decomposition treatment, while the content of carbon contained in the conductive film is increased. In addition, the condensate (B) (dispersant) present on the surface of the conductive film is removed, and more carbon is exposed on the surface of the conductive film. Therefore, the catalytic activity of the conductive film is improved.
[0084] (electrode) The electrode of the present invention is obtained by using the conductive film of the present invention. The electrode of the present invention is suitably used in organic solar cells such as dye-sensitized solar cells (DSC), organic thin-film solar cells, and perovskite solar cells. The electrode of the present invention will be described by taking a DSC as an example. A DSC usually has a structure in which a photoelectrode, an electrolyte layer, and a counter electrode are arranged in this order. A photoelectrode is an electrode that can emit electrons to an external circuit by receiving light. A photoelectrode usually has a photoelectrode substrate in which a conductive film is formed on a base material, a porous semiconductor fine particle layer formed on the photoelectrode substrate, and a sensitizing dye layer formed by adsorbing a sensitizing dye on the surface of the porous semiconductor fine particle layer. The electrolyte layer is a layer that separates the photoelectrode and the counter electrode and facilitates efficient charge transfer. The counter electrode is an electrode for efficiently transferring electrons received from an external circuit to the electrolyte layer. The counter electrode usually has a counter electrode substrate formed of a conductive film on a base material, and a catalyst layer formed on the counter electrode substrate.
[0085] <Photoelectrode> In the present invention, the photoelectrode usually has a photoelectrode substrate in which the conductive film of the present invention is formed on a base material, a porous semiconductor fine particle layer formed on this photoelectrode substrate, and a sensitizing dye layer formed by adsorbing a sensitizing dye to the surface of the porous semiconductor fine particle layer.
[0086] <Base material> The substrate is not particularly limited in shape, constituent material, and size (thickness, etc.) as long as the dispersion of the present invention can be applied thereon and the substrate can support the resulting conductive film, and can be appropriately selected depending on the intended use. Among the materials constituting the substrate, inorganic materials include metals such as titanium, stainless steel, aluminum, iron, gold, and silver, and glass. Organic materials include carbon materials and plastic substrate materials. Plastic substrate materials are preferred from the viewpoint of improving the adhesion (adhesiveness) with the conductive film and the stretchability and flexibility of the conductive film. Furthermore, as the plastic substrate material, materials that are highly heat-resistant, excellent in chemical resistance and gas barrier properties, and low cost are preferred. In addition, the plastic substrate material may be uncolored and transparent. Specific examples of such plastic substrate materials include polyesters (polyethylene terephthalate (PET), polyethylene naphthalate (PEN), etc.), styrenes (syndiotactic polystyrene (SPS), etc.), polyphenylene sulfide (PPS), polycarbonate (PC), polyarylate (PAr), polysulfone (PSF), polyestersulfone (PES), polyetherimide (PEI), transparent polyimide (PI), cycloolefin copolymers (trade name "Arton" (registered trademark), etc.), alicyclic polyolefins (trade name "ZEONOR" (registered trademark), etc.), polycarbonate, polyamide, polyurethane, polymethyl methacrylate, cellulose, triacetyl cellulose, aramid, polypropylene, polyethylene, polylactic acid, polyvinyl chloride, alicyclic acrylic resins, etc. Among these, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and alicyclic polyolefins are particularly preferred from the viewpoints of chemical stability and cost. When a plastic substrate material is used as the substrate, the preferred thickness of the substrate is not particularly limited and can be in a range from a medium thickness to a very thin thickness. In such a case, the thickness of the substrate is preferably 1 μm or more, more preferably 5 μm or more, and particularly preferably 20 μm or more, and is preferably 1000 μm or less, more preferably 500 μm or less, and particularly preferably 250 μm or less. As the substrate, a substrate on which a known conductive film other than the conductive film of the present invention is formed, or a substrate having an undercoat layer of resin or the like may be used. Examples of the known conductive film include metals such as platinum, gold, silver, copper, aluminum, indium, and titanium; conductive metal oxides such as tin oxide and zinc oxide; composite metal oxides such as indium-tin oxide (ITO), indium-zinc oxide (IZO), and fluorine-doped tin oxide (FTO); carbon materials such as carbon nanotubes, carbon nanobats, graphene, fullerene, and diamond-like carbon (DLC); and combinations of two or more of these. The thickness of these is not particularly limited, but is usually 0.001 μm or more, preferably 0.01 μm or more, more preferably 0.1 μm or more, and 100 μm or less, preferably 50 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less. The surface of the substrate on which the dispersion of the present invention is applied or on which a porous semiconductor fine particle layer described below is formed may be subjected to a surface hydrophilization treatment such as glow discharge treatment, corona discharge treatment or UV ozone treatment. In addition, the surface of the substrate to which the dispersion of the present invention is applied or the opposite surface thereof may be subjected to a hard coat treatment imparting abrasion resistance, high surface hardness, solvent resistance, stain resistance, fingerprint resistance, anti-reflection properties, etc., a UV-cut layer, an organic and / or inorganic oxygen / moisture barrier layer, an easy-slip layer, an easy-adhesion layer, or the like. The photoelectrode substrate constituting the photoelectrode in the present invention is not particularly limited, and may be (1) a substrate / conductive film of the present invention laminated in this order, (2) a substrate / conductive film of the present invention / known conductive film laminated in this order, or (3) a substrate / known conductive film / conductive film of the present invention laminated in this order, but the embodiment (3) is preferred because of stable performance and ease of manufacture. Among them, a substrate (e.g., PEN) / known conductive film (e.g., ITO) / conductive film of the present invention (e.g., CNT film) laminated in this order is more preferred because of excellent conductivity and durability.
[0087] <<Porous semiconductor particle layer>> Hereinafter, a porous semiconductor fine particle layer including a sensitizing dye layer will be illustrated. The porous semiconductor fine particle layer is a porous layer containing semiconductor fine particles. The porous layer increases the amount of sensitizing dye adsorbed, making it easier to obtain a dye-sensitized solar cell with high conversion efficiency.
[0088] Examples of the semiconductor fine particles include particles of metal oxides such as titanium oxide, zinc oxide, and tin oxide. Titanium oxide is preferred as the semiconductor fine particles. A layer in which titanium oxide is used as the semiconductor fine particles is called a titanium oxide layer.
[0089] The particle diameter of the semiconductor fine particles (average particle diameter of primary particles) is preferably 1 nm or more, and is usually 500 nm or less, preferably 150 nm or less, and more preferably 80 nm or less. The particle diameter may be 1 to 100 nm, and may be used alone or in combination of two or more. Particles larger than 100 nm and particles smaller than 500 nm may be further combined. By using particles with a small particle diameter of 100 nm or less, the specific surface area of the porous semiconductor fine particle layer can be increased, and by using particles larger than 100 nm, the porous semiconductor fine particle layer can be given scattering properties, allowing efficient use of incident light from the solar cell.
[0090] The thickness of the porous semiconductor fine particle layer is usually 0.01 μm or more, preferably 0.1 μm or more, more preferably 5 μm or more, and preferably 30 μm or less, more preferably 10 μm or less, which allows efficient use of incident light in the DSC.
[0091] The method for forming the porous semiconductor fine particle layer is not particularly limited, and a known method can be appropriately selected and used. For example, the porous semiconductor fine particle layer can be formed by a known method such as a pressing method, a hydrothermal decomposition method, a migration electrodeposition method, an aerosol deposition method (AD method), a transfer method, or a binder-free coating method.
[0092] The heating temperature when forming the porous semiconductor particle layer is usually 100° C. or higher and 600° C. or lower, and when a plastic substrate is used, the heating temperature is preferably 200° C. or lower, and more preferably 160° C. or lower. A buffer layer may be formed between the porous semiconductor fine particle layer and the conductive layer of the substrate. The composition and manufacturing method of the buffer layer are not particularly limited, but it is formed, for example, by sputtering or CVD deposition of a metal oxide such as titanium, tin, or niobium, or by applying an alkoxy compound or chloride of the corresponding metal element to the conductive layer. The thickness of the buffer layer is usually 0.001 nm to 1000 nm, preferably 0.01 nm to 10 nm. Within this range, it is possible to improve the electron back charge reaction, the adhesion of the porous semiconductor fine particle layer to the conductive layer, and the reduction of the series resistance of the module.
[0093] <<Sensitizing dye layer>> The sensitizing dye layer is a layer in which a compound (sensitizing dye) capable of being excited by light to donate electrons to the porous semiconductor fine particle layer is adsorbed on the surface of the porous semiconductor fine particle layer.
[0094] The sensitizing dye is not particularly limited, and can be appropriately selected from known sensitizing dyes for dye-sensitized solar cells, and examples thereof include organic dyes such as cyanine dyes, merocyanine dyes, oxonol dyes, xanthene dyes, squarylium dyes, polymethine dyes, coumarin dyes, riboflavin dyes, and perylene dyes; metal complex dyes such as phthalocyanine complexes and porphyrin complexes of metals such as iron, copper, and ruthenium; etc. Representative examples of sensitizing dyes include N3, N719, N749, D102, D131, D150, N205, HRS-1, MK-2, SK-1, and CYC. It is preferable that the organic solvent (dye solvent) in which the dye is dissolved be degassed, purified by distillation, or dried in advance in order to remove moisture and gas present in the solvent. For example, preferred solvents include alcohols such as methanol, ethanol, and propanol; nitriles such as acetonitrile; halogenated hydrocarbons; ethers; amides; esters; carbonates; ketones; hydrocarbons; aromatics; and nitromethane. It may also contain a co-adsorbent such as a carboxylic acid having a steroid skeleton, such as cholic acid, deoxycholic acid, etc. These dyes, solvents and co-adsorbents may be used alone or in combination of two or more kinds.
[0095] The method for forming the sensitizing dye layer is not particularly limited, and a known method can be appropriately selected and used. For example, the sensitizing dye layer can be formed by known methods such as a method of immersing the porous semiconductor fine particle layer in a solution of the sensitizing dye or a method of applying a solution of the sensitizing dye onto the porous semiconductor fine particle layer. After impregnation or application, it is preferable to wash the substrate including the porous semiconductor layer with the above-mentioned dye solvent to wash off excess dye. After forming or washing the sensitizing dye layer, it is sufficient to dry it by known methods such as heating, leaving it in the air, and drying under reduced pressure.
[0096] <Counter electrode> In the present invention, the counter electrode usually comprises a counter electrode substrate in which the conductive film of the present invention is formed on a base material, and a catalyst layer formed on this counter electrode substrate. In the present invention, the counter electrode substrate constituting the counter electrode is not particularly limited, and may be laminated in the order of (1) substrate / conductive film of the present invention, (2) substrate / conductive film of the present invention / known conductive film, or (3) substrate / known conductive film / conductive film of the present invention, but the above-mentioned embodiment (3) is preferred because of its stable performance and ease of manufacture. Some conductive films exhibit catalytic activity depending on the material, and in that case, the counter electrode substrate having the above-mentioned configurations (1) to (3) can be used as a counter electrode as it is. For example, when the conductive film of the present invention is a CNT film, the conductive film exhibits catalytic activity and also serves as a catalyst layer. As such a counter electrode, a substrate (e.g., PEN) / known conductive film (e.g., ITO) / conductive film of the present invention (e.g., CNT film) laminated in this order is more preferred because of its excellent catalytic activity and durability. The substrate and known conductive film may be the same as those described in the description of the photoelectrode, and the preferred embodiments thereof are also the same.
[0097] <<Catalyst layer>> The catalyst layer functions as a catalyst when transferring electrons from the counter electrode to the electrolyte layer described later in an organic solar cell. As described above, the catalyst layer can be formed from the conductive film (CNT film) of the present invention, but a known catalyst layer can also be appropriately selected and used. For example, it is preferable that the catalyst layer contains a conductive polymer, a carbon material, precious metal particles, or both a carbon material and precious metal particles, which have catalytic activity.
[0098] [Conductive polymer] Examples of the conductive polymer include polythiophenes such as poly(thiophene-2,5-diyl), poly(3-butylthiophene-2,5-diyl), poly(3-hexylthiophene-2,5-diyl), and poly(2,3-dihydrothieno-[3,4-b]-1,4-dioxin) (PEDOT); polyacetylene and its derivatives; polyaniline and its derivatives; polypyrrole and its derivatives; and polyphenylene vinylenes such as poly(p-xylenetetrahydrothiophenium chloride), poly[(2-methoxy-5-(2'-ethylhexyloxy))-1,4-phenylene vinylene], poly[(2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene)], and poly[2-2',5'-bis(2''-ethylhexyloxy)phenyl]-1,4-phenylene vinylene]. [Precious metal particles] The noble metal particles are not particularly limited as long as they have catalytic activity, and known noble metal particles can be appropriately selected and used. For example, platinum metal, palladium metal, ruthenium metal, etc., can be used alone or as an alloy, or as a core-shell structure. The particle size of these particles is not particularly limited, but is usually 0.01 nm to 50 nm in diameter.
[0099] The method for forming the catalyst layer is not particularly limited, and a known method can be appropriately selected and used. For example, a mixed liquid obtained by dissolving or dispersing a conductive polymer, a carbon material, precious metal particles, or both a carbon material and precious metal particles in a suitable solvent is applied or sprayed onto the conductive film, and the solvent of the mixed liquid is dried. When a carbon material or precious metal particles is used, a binder may be further contained in the mixed liquid. As the binder, it is preferable to use a polymer compound having a functional group such as a hydroxyl group, a carboxyl group, a sulfonyl group, a phosphoric acid group, or a sodium salt of these functional groups, in terms of the dispersibility of the carbon material and the adhesion to the substrate.
[0100] The thickness of the catalyst layer is preferably 0.005 μm or more and 100 μm or less, more preferably 0.01 μm to 50 μm, even more preferably 0.1 μm to 10 μm, and particularly preferably 0.5 μm to 5 μm. Within this range, the catalyst layer has low film strength, adhesion, catalytic performance, and series resistance as a solar cell module, and the solar cell has excellent performance.
[0101] <Electrolyte layer> The electrolyte layer is a layer that separates the photoelectrode and the counter electrode and allows charge transfer to occur efficiently. The electrolyte layer is not particularly limited and may be a solid, liquid, or semi-solid such as a gel. The electrolyte layer usually contains a supporting electrolyte, a redox pair (a pair of chemical species that can be reversibly converted into an oxidized form and a reduced form in an oxidation-reduction reaction), a solvent, etc.
[0102] <<Supporting electrolyte>> Examples of the supporting electrolyte include (i) salts of alkali metals or alkaline earth metals, such as lithium iodide and sodium iodide; (ii) ionic liquids containing cations, such as pyridinium salts, imidazolium ions, compounds having a quaternary nitrogen atom as a spiro atom, and quaternary ammonium ions.
[0103] <<Redox pair>> Any known redox couple can be used as long as it can reduce the oxidized sensitizing dye. Examples of the redox couple include iodine compound-iodine, bromine compound-bromine, zinc complex, iron complex, and cobalt complex.
[0104] <<Solvent>> The solvent may be any known solvent for forming an electrolyte layer. Examples of the solvent include highly polar solvents such as acetonitrile, methoxyacetonitrile, methoxypropionitrile, N,N-dimethylformamide, ethylmethylimidazolium bistrifluoromethylsulfonylimide, propylene carbonate, glycol ether, and γ-butyrolactone. From the viewpoint of reliability of the solar cell module, aprotic solvents are preferred.
[0105] The method for forming the electrolyte layer is not particularly limited, and a known method can be appropriately selected and used. For example, the electrolyte layer can be formed by applying a solution (electrolyte) containing the components of the electrolyte layer onto the photoelectrode and / or the counter electrode under atmospheric pressure or reduced pressure, or by preparing a cell having a photoelectrode and a counter electrode and injecting the electrolyte into the gap between them.
[0106] (Solar Cell) The solar cell of the present invention is provided with the electrode of the present invention described above. The solar cell of the present invention is not particularly limited as long as it is provided with the electrode of the present invention. Examples of the solar cell of the present invention include organic solar cells such as the dye-sensitized solar cell, organic thin-film solar cell, and perovskite solar cell described above. Examples of perovskite solar cells are described in, for example, JP-A-2014-049631, JP-A-2015-046583, and JP-A-2016-009737. In addition to such organic solar cells, there are also solar cells classified into, for example, crystalline silicon solar cells such as single crystal silicon solar cells, polycrystalline silicon solar cells, microcrystalline silicon solar cells, and multi-bonded silicon solar cells; amorphous silicon solar cells; and compound solar cells such as GaAs solar cells, CIS solar cells, and CdTe solar cells, depending on the type of semiconductor substrate. Furthermore, the solar cell of the present invention is not limited to one that uses the sun as a light source, but may also use, for example, indoor lighting as a light source. The solar cell of the present invention has a high conversion efficiency because it is provided with the electrode of the present invention. Since such characteristics are particularly utilized, the solar cell of the present invention is preferably used as a portable solar cell or an indoor solar cell. A solar cell module may be constructed using one or more solar cell cells of the present invention. The shape of the solar cell is not particularly limited, and may be Z-type, W-type, parallel type, current collector array type, monolithic type, etc. One or more of these solar cells may be combined and connected in series or parallel to form a plurality of connections. The connection method may be any known means, and may be appropriately selected from solder, metal plate, cable, flat cable, flexible substrate, cable, etc. A solar cell or module may be provided with an extraction electrode in order to extract current from the module. There are no particular limitations on the position, material, or manufacturing method of the extraction electrode, and it may be implemented by a known method. Materials that can be used include metals such as aluminum, nickel, stainless steel, copper, gold, silver, and solder, as well as pastes such as carbon, and conductive tapes. The extraction electrodes may be appropriately manufactured so that a total of two electrodes are connected to each of the negative and positive electrodes of the solar cell module. The electrode may also be provided with a current collector wiring that efficiently collects electrons generated from the solar cell. The current collector wiring is not particularly limited, and any known current collector wiring may be appropriately selected and used. The current collector wiring may be produced by, for example, a sputtering method, a vapor deposition method, a plating method, or a coating method such as an inkjet method or a screen printing method using a conductive paste containing photocurable and / or thermosetting silver or carbon. A protective seal that protects the current collector wiring from the electrolyte may be used for this current collector wiring. As the protective seal, a thermosetting and / or photocurable resin such as low polarity acrylic resin, polyisobutylene, polyisoprene, polybutadiene, and epoxy resin, or a thermoplastic resin such as Himilan may be used. Furthermore, insulating spacer particles, conductive fine particles, etc. can be used to separate the electrodes of the solar cell module and to electrically connect the cells. These may be contained in a sealing resin, such as a heat and / or light curing resin or a thermoplastic resin such as Himilan, which seals the electrolyte of the solar cell module and / or bonds between the electrodes. As an example of such a solar cell module, an example of a DSC module is shown in FIG. 1. The DSC module 100 is a DSC module including a connector formed by connecting a plurality of (four in the illustrated example) cells partitioned by a partition wall 8 in series, and has a Z-shaped integrated structure. The DSC module 100 has a structure in which a first substrate 3 including a first substrate 1 and a plurality of (four in the illustrated example) photoelectrodes 2 serving as first electrodes spaced apart from one another on the first substrate 1, and a second substrate 7 including a second substrate 5 and a plurality of (four in the illustrated example) counter electrodes 6 serving as second electrodes spaced apart from one another on the second substrate 5, are bonded together with a partition wall 8 interposed between the first substrate 3 and the second substrate 7, such that the photoelectrodes 2 and counter electrodes 6 forming each cell face each other via an electrolyte layer 4 serving as a functional layer (i.e., to form a cell), and between adjacent cells, the photoelectrode 2 of one cell and the counter electrode 6 of the other cell are electrically connected via a cell connection part 9 made of a conductive resin composition. Each cell of the DSC module 100 includes a photoelectrode 2, a counter electrode 6 facing the photoelectrode 2, and an electrolyte layer 4 provided between the photoelectrode 2 and the counter electrode 6. The DSC module 100 also includes a first extraction electrode 12A connected to the photoelectrode conductive layer 21 constituting the photoelectrode 2, and a second extraction electrode 12B connected to the counter electrode conductive layer 61 constituting the counter electrode 6. EXAMPLES
[0107] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. Measurements and evaluations in the present examples were performed by the following methods.
[0108] <(1) Dispersibility of the dispersion liquid (CNT and / or KB paste)> First, we prepared a transparent conductive plastic film (thickness: 186 μm, surface resistance of the conductive layer side: 15 Ω / □) consisting of a conductive layer made of indium-tin oxide (ITO) formed on a substrate made of polyethylene naphthalate (PEN). Next, the CNT and / or KB paste (dispersion liquid) obtained in each Example or Comparative Example was dispersed on the surface of the transparent conductive plastic film on which the conductive layer was formed using a wet jet mill (manufacturer: Yoshida Kikai Co., Ltd., product name: Nanovaita), and then coated with an applicator (manufacturer: Matsuo Sangyo Co., Ltd.) under a gap of 30 μm to form a coating film of carbon nanostructures (CNT and / or KB). The state of the formed coating film was visually observed, and the dispersibility of the CNT and / or KB paste was evaluated according to the following criteria. The evaluation results are shown in Table 1. <<Evaluation Criteria>> A: No agglomerates and no streaks on the coated surface. B: There are aggregates and / or streaks on the applied surface. C: Too many aggregates and unable to form a coating.
[0109] <(2) Screen printability of dispersion (CNT and / or KB paste)> First, we prepared a transparent conductive plastic film (thickness: 186 μm, surface resistance of the conductive layer side: 15 Ω / □) consisting of a conductive layer made of indium-tin oxide (ITO) formed on a substrate made of polyethylene naphthalate (PEN). Next, the CNT and / or KB paste (dispersion liquid) obtained in each Example or Comparative Example was applied to the surface of the transparent conductive plastic film on which the conductive layer was formed by screen printing using a 100 mesh screen, and dried in an inert oven (manufactured by Yamato Scientific Co., Ltd.) in air at 125°C for 15 minutes to form a coating film. 2 The areas were visually observed and the screen printability of the CNT paste was evaluated according to the following criteria. The evaluation results are shown in Table 1. Note that the fewer pinholes found in the visual observation of the coating film, the better the screen printability of the CNT and / or KB paste. <<Evaluation Criteria>> A: No pinholes B: Pinholes with a diameter of 1 mm or less have occurred C: Pinholes with a diameter of more than 1 mm have occurred.
[0110] <(3) Adhesion of conductive film to substrate> First, we prepared a transparent conductive plastic film (thickness: 186 μm, surface resistance of the conductive layer side: 15 Ω / □) consisting of a conductive layer made of indium-tin oxide (ITO) formed on a substrate made of polyethylene naphthalate (PEN). Next, the CNT and / or KB paste (dispersion liquid) obtained in each Example or Comparative Example was applied by screen printing using a 100 mesh screen onto the surface of the transparent conductive plastic film on which the conductive layer was formed, and then dried in an inert oven (manufactured by Yamato Scientific Co., Ltd.) at 125°C in air for 15 minutes to form a coating film. After that, rinsing was performed using the rinsing liquid of each Example or Comparative Example. After rinsing, the coating film was checked for "surface swelling" and "peeling of the coating surface" at any three points (1 cm2 at each point) on the formed coating film. 2 The adhesion of the conductive film to the substrate was evaluated according to the following criteria. The evaluation results are shown in Table 1. <<Evaluation criteria>> A: No "surface swelling" or "peeling of the coating surface" was observed in any of the three locations. B: No "surface blistering" or "peeling of the coated surface" was observed at two of the three locations, and only one total was observed at the one location where either "surface blistering" or "peeling of the coated surface" was observed. C: Cases other than A and B above.
[0111] <(4) Energy conversion efficiency of solar cells> The light source used was a simulated solar irradiation device (PEC-L11, manufactured by Peccel Technologies) equipped with a 150 W xenon lamp light source and an AM1.5G filter. The light intensity was 1 sun (AM1.5G, 100 mW / cm2). 2 (Class A of JIS C8912). The fabricated solar cell was connected to a source meter (2400 type source meter, manufactured by Keithley Instruments) and the following current-voltage characteristics were measured. Under 1 sun of light irradiation, the output current was measured while changing the bias voltage from 0 V to 0.8 V in 0.01 V increments. The output current was measured by integrating the value from 0.05 seconds to 0.15 seconds after changing the voltage at each voltage step. Measurements were also performed while changing the bias voltage in the reverse direction from 0.8 V to 0 V, and the average value of the measurements in the forward and reverse directions was taken as the photocurrent. From the measurement results of the current-voltage characteristics, the energy conversion efficiency (%) was calculated. The energy conversion efficiency of the solar cells was evaluated according to the following criteria. The evaluation results are shown in Table 1. <<Evaluation Criteria>> A: Conversion efficiency is 4.0% or more B: Conversion efficiency is 3.5% or more and less than 4.0% C: Conversion efficiency is 3.0% or more but less than 3.5% D: Conversion efficiency is less than 3.0%
[0112] <(5) Weight average molecular weight (Mw) and molecular weight distribution ( Mw / Mn ) Measurement> The weight average molecular weight (Mw) and molecular weight distribution (Mw) of the condensate (B) (dispersant) were measured using gel permeation chromatography (GPC) (Nihon Waters, Alliance HPLC system) under the following conditions. Mw / Mn The weight average molecular weight (Mw) was calculated based on standard polyethylene glycol. <Measurement conditions> Column: "SHODEX GF1G-7B: 1 column" and "SHODEX GF310HQ (packing material particle size: 5 μm, inner diameter (ID): 30 cm): 1 column" were connected in series and used. Eluent: LiCl aqueous solution (0.05 mol / L) / acetonitrile = 40 / 60 Flow rate: 0.6mL / min Column temperature: 30℃ Detector: Refractive index (RI) Injection volume: 50μL
[0113] <(6) Measurement of copolymerization ratio (molar ratio) of condensate (B) (dispersant)> 1 The copolymerization ratio was determined from the ratio of signal intensities characteristic of each monomer at a sample concentration of 1% using H-NMR (manufacturer: Bruker Japan Co., Ltd., product name: AVANCEIII (500MHz)). CDCl3 was used as the deuterated solvent.
[0114] <Preparation of single-walled carbon nanotubes (SGCNTs)> In accordance with International Publication No. 2006 / 011655, single-walled carbon nanotubes (SGCNTs) obtained by the super-growth method were synthesized, and the following was obtained. The length, diameter and diameter distribution were determined by TEM using the average values of 20 randomly selected particles, the specific surface area was determined by the BET specific surface area using nitrogen, and the G / D ratio was determined by Raman spectroscopy. Length: 500μm Diameter: 3.5nm: Diameter distribution (3σ / Av): 0.57 Specific surface area: 880m 2 / g G / D ratio: 4.0 CH elemental analysis: C:99.9%, H0.1%
[0115] <Preparation of single-walled carbon nanotubes (HiPco)> Single-walled carbon nanotubes (manufacturer: NanoIntegris, product name: HiPco (registered trademark)) were prepared.
[0116] <Preparation of carbon particles (KB)> Ketjen black (manufacturer: Lion Specialty Chemicals Co., Ltd., product name: EC600JD, primary particle diameter: 34 nm) was prepared as carbon particles.
[0117] <Synthesis Example 1: Preparation of Condensate (B) (Dispersant A)> A reaction vessel was charged with 125.1 g (0.50 mol) of 4,4'-dihydroxydiphenyl sulfone (DSF) (component A: hydroxyphenol compound) and 87.0 g (0.50 mol) and 210.4 g of water (the amount of water that would give a solids concentration of 50 mass % after the dropwise addition of component C described below), and 68.3 g (0.82 mol) of a 48 mass % aqueous sodium hydroxide solution (component C) was added dropwise. Next, 81.2 g (1.00 mol) of 37% by mass formaldehyde aqueous solution (component D) was dropped under a temperature condition of 80°C, and the mixture was allowed to react under reflux (98°C to 100°C) for 4 hours. Before the reaction was completed, 368.2 g of water (an amount of water that would result in a monomer (component A + component B) concentration of 25% by mass) was added to obtain 970 g of an aqueous solution containing dispersant A. The weight average molecular weight of this dispersant A was measured by GPC (gel permeation chromatography) to be 790 (standard polyethylene glycol equivalent), 1 1 H-NMR measurement revealed that the molar ratio of component A (hydroxyphenol compound):component B (aromatic sulfonic acid compound) was 1:1.
[0118] <Synthesis Example 2: Preparation of Condensate (B) (Dispersant B)> The same procedure as in Synthesis Example 1 was carried out, except that the reaction time was 8 hours instead of 4 hours. The weight average molecular weight of this dispersant B was measured by GPC (gel permeation chromatography) and found to be 2400 (standard polyethylene glycol equivalent). 1 1 H-NMR measurement revealed that the molar ratio of component A (hydroxyphenol compound):component B (aromatic sulfonic acid compound) was 1:1.
[0119] <Synthesis Example 3: Preparation of Condensate (B) (Dispersant C)> The same procedure as in Synthesis Example 1 was carried out, except that the amounts (molar ratios) of the components charged in the above Synthesis Example 1 were changed to the amounts (molar ratios) shown below. The weight average molecular weight of this dispersant C was measured by GPC (gel permeation chromatography) and found to be 1130 (standard polyethylene glycol equivalent). 1 1 H-NMR measurement revealed that the molar ratio of component A (hydroxyphenol compound):component B (aromatic sulfonic acid compound) was 1:3. <<Feed amount (molar ratio) of Synthesis Example 3>> 4,4'-dihydroxydiphenylsulfone (component A):p-phenolsulfonic acid (component B) = 1:3 4,4'-Dihydroxydiphenylsulfone (Component A): 48% by mass aqueous sodium hydroxide solution (Component C) = 1:0.75 (4,4'-dihydroxydiphenyl sulfone (component A) + p-phenolsulfonic acid (component B)): (37% by mass formaldehyde aqueous solution (component D)) = 1:1.25
[0120] <Synthesis Example 4: Preparation of Condensate (B) (Dispersant D)> The same procedure as in Synthesis Example 1 was carried out, except that the amounts (molar ratios) of the components charged in the above Synthesis Example 1 were changed to the amounts (molar ratios) shown below. The weight average molecular weight of Dispersant D was measured by GPC (gel permeation chromatography) and found to be 870 (standard polyethylene glycol equivalent). 1 1 H-NMR measurement revealed that the molar ratio of component A (hydroxyphenol compound):component B (aromatic sulfonic acid compound) was 3:1. <<Feed amount (molar ratio) of Synthesis Example 4>> 4,4'-dihydroxydiphenylsulfone (component A):p-phenolsulfonic acid (component B) = 3:1 4,4'-Dihydroxydiphenylsulfone (Component A): 48% by mass aqueous sodium hydroxide solution (Component C) = 1:0.75 (4,4'-dihydroxydiphenyl sulfone (component A) + p-phenolsulfonic acid (component B)): (37% by mass formaldehyde aqueous solution (component D)) = 1:1.25
[0121] <Synthesis Example 5: Preparation of Condensate (B) (Dispersant E)> The same procedure as in Synthesis Example 1 was carried out, except that the reaction time was 16 hours instead of 4 hours. The weight average molecular weight of this dispersant E was measured by GPC (gel permeation chromatography) and found to be 3,200 (standard polyethylene glycol equivalent).1 1 H-NMR measurement revealed that the molar ratio of component A (hydroxyphenol compound):component B (aromatic sulfonic acid compound) was 1:1.
[0122] <Preparation of Dispersants F to I> The following dispersants F to I were prepared. Dispersant F: Phenol sulfonic acid resin (Konishi Chemical Industry Co., Ltd.) Dispersant G: β-naphthalenesulfonic acid formalin condensate sodium salt (manufactured by Kao Corporation, product name: Demol RN) Dispersant H: Sodium phenolsulfonate (manufactured by Junsei Chemical Co., Ltd.) Dispersant I: Norylphenol (manufactured by Nicca Chemical Co., Ltd.)
[0123] Example 1 <Preparation of Dispersion Liquid> 140 g of pure water and hydrochloric acid were added to a 500 mL plastic bottle to adjust the pH to 2.0, and 60 g of ethanol (solvent (C)) was further added to prepare 200 g of solution. To this solution, a 30 mass% alkaline solution of dispersant A prepared so as to have the mass ratio (nanocarbon / dispersant) (carbon material (A) / condensate (B)) in Table 1 was added, and further SGCNTs were added to prepare a wet mixture with 0.40 mass% SGCNT and pH of 2.0. This mixture was stirred with a homomixer at 6,000 rpm for 30 minutes while cooling the polyethylene bottle to 25° C. in a water bath to obtain a crude dispersion. The obtained crude dispersion was treated with a wet jet mill (manufacturer: Yoshida Kikai Co., Ltd., product name: Nanovaita) for 10 passes at 100 MPa while cooling the dispersion to 25° C., to obtain a CNT paste as a dispersion. This CNT paste (dispersion liquid) was used for various evaluations.
[0124] <Preparation of dye solution> As the dye solution, a sensitizing dye solution (concentration: 0.4 mM) was prepared. A ruthenium complex (manufactured by Solaronics: product name N719) was used as the sensitizing dye, and a solvent of acetonitrile:tert-butanol=1:1 was used as the solvent.
[0125] <Fabrication of photoelectrode> A 5 mM titanium isopropoxide solution in isopropyl alcohol was applied onto an ITO-PEN film (50 mm x 50 mm, 15 Ω / □) by bar coating, and dried in an inert oven (Yamato Scientific Co., Ltd.) at 150 °C for 15 minutes. A thermosetting Ag paste (Toyochem Co., Ltd.) was printed using a screen printer (SFA-PC610CTN, made by ceria) and heated in an inert oven (Yamato Scientific Co., Ltd.) at 130 °C for 30 minutes to form an extraction electrode (thickness 8 μm). Furthermore, a water-based titanium oxide paste (PECC-AW1-01, made by Pexel Technologies Co., Ltd.) was applied using a screen printer and dried in an inert oven (Yamato Scientific Co., Ltd.) at 150 °C for 15 minutes to form a porous semiconductor layer (the thickness of the titanium oxide layer was 8 μm). The substrate on which this porous semiconductor layer was formed was placed in a dye solution (50 cm tray) and immersed for 2 hours at 40° C. After immersion, it was washed with an ethanol solution and dried under reduced pressure at 40° C. for 24 hours to prepare a photoelectrode.
[0126] <Preparation of counter electrode> The CNT paste (dispersion) prepared above was applied onto an ITO-PEN film (50 mm x 50 mm, 15 Ω / □) by screen printing using a 100-mesh screen, and dried in an inert oven (manufactured by Yamato Scientific Co., Ltd.) in air at 125°C for 15 minutes to form a coating film. After that, the substrate coated with the CNT paste (dispersion) was washed using an alkaline rinse solution (NaOH solution: pH 10), and dried at 60°C under reduced pressure for 2 hours to prepare a counter electrode of a PEN substrate (PEN + ITO + conductive film of the present invention) on which a conductive film of the present invention was formed.
[0127] <Fabrication of organic solar cells> In a vacuum lamination device, a sealant (polybutylene-based photocurable resin and 8% by mass of insulating spacer resin (25 μm)) was applied to the photoelectrode fabricated by a dispenser so that the sealant width after lamination would be 0.9 mm and the height would be 30 μm, and then an electrolyte solution was applied to the titanium oxide layer (porous semiconductor fine particle layer). The counter electrode was placed in the vacuum lamination device, and the electrodes were laminated in a vacuum, and UV irradiation was performed using a metal halide lamp with an integrated light intensity of 3000 mJ / cm. 2 The vacuum was released to atmospheric pressure, and the organic solar cell was taken out.
[0128] (Examples 2 to 9, Comparative Examples 1 to 4) Instead of preparing the dispersion (CNT paste) under the conditions shown in Example 1 in Table 1, in Example 1, the dispersion and the counter electrode were prepared under the conditions shown in any one of Examples 2 to 9 and Comparative Examples 1 to 4 in Table 1. Except for this, the preparation of the dispersion, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1. As the "neutral rinse liquid" in Table 1, ion-exchanged water (pH 7.0) was used. Specifically, the following procedure was carried out. <Example 2> Except for using a neutral rinse instead of the alkaline rinse in Example 1, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1. <Example 3> Except for using single-walled carbon nanotubes (HiPco) instead of single-walled carbon nanotubes (SGCNT) in Example 2, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Example 4> Except for using 4.00 mass% of Ketjen Black (KB) instead of 0.40 mass% of single-walled carbon nanotubes (SGCNT) in Example 2, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Example 5> Except for using a mixture of single-walled carbon nanotubes (SGCNT) and Ketjen Black (KB) (mixture ratio (mass%): 80 / 20) instead of single-walled carbon nanotubes (SGCNT) in Example 1, the preparation of a dispersion liquid, preparation of a dye solution, preparation of a photoelectrode, preparation of a counter electrode, preparation of an organic solar cell, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1. <Example 6> Except for using dispersant B instead of dispersant A in Example 2, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Example 7> Except for using dispersant C instead of dispersant A in Example 2, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Example 8> Except for using dispersant D instead of dispersant A in Example 2, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Example 9> Except for using dispersant E instead of dispersant A in Example 2, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Comparative Example 1> A dispersion was prepared in the same manner as in Example 2, except that Dispersant F was used in an amount 20 times the mass of the carbon material instead of Dispersant A, which was 2.5 times the mass of the carbon material in Example 2. The results are shown in Table 1. Note that, due to poor dispersibility, a coating film could not be obtained by screen printing, and other evaluations were not performed. <Comparative Example 2> Except for using 20 times the mass of the carbon material as dispersant G instead of 2.5 times the mass of the carbon material as dispersant A in Example 2, the preparation of the dispersion liquid, preparation of the dye solution, preparation of the photoelectrode, preparation of the counter electrode, preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Comparative Example 3> Except for using 20 times the mass of the carbon material as dispersant H instead of 2.5 times the mass of the carbon material as dispersant A in Example 2, the preparation of the dispersion liquid, preparation of the dye solution, preparation of the photoelectrode, preparation of the counter electrode, preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1. <Comparative Example 4> Except for using 20 times the mass of the carbon material as dispersant I instead of 2.5 times the mass of the carbon material as dispersant A in Example 2, the preparation of the dispersion liquid, the preparation of the dye solution, the preparation of the photoelectrode, the preparation of the counter electrode, the preparation of the organic solar cell, and various evaluations were performed in the same manner as in Example 2. The results are shown in Table 1.
[0129] [Table 1]
[0130] From Table 1, it can be seen that by using the dispersions of Examples 1 to 9, it is possible to improve the coatability (wettability) to the substrate (improve screen printability), and form a conductive film with high adhesion to the substrate. [Industrial Applicability]
[0131] According to the present invention, it is possible to provide a dispersion liquid capable of improving the coatability (wettability) to a substrate and forming a conductive film having high adhesion to the substrate. Furthermore, according to the present invention, it is possible to provide a conductive film having high adhesion to a substrate and a method for producing the same, an electrode including the conductive film and having high conductivity, and a solar cell including the electrode and having high conversion efficiency. [Explanation of symbols]
[0132] 1 First base material 2. Photoelectrode 3 First board 4 Electrolyte layer 5 Second base material 6 Counter electrode 7 Second board 8 Bulkhead 9 Cell connection part (conductive resin composition) 12A First extraction electrode 12B Second extraction electrode 21 Conductive layer for photoelectrodes 22 Porous semiconductor particle layer 61 Counter electrode conductive layer 62 Catalyst layer 100 DSC Module
Claims
1. A carbon material (A), a condensate (B) of an aromatic sulfonic acid compound, a hydroxyphenol compound, and an aldehyde compound, and a solvent (C), The aromatic sulfonic acid compound is at least one selected from the group consisting of p-phenolsulfonic acid, o-phenolsulfonic acid, phenoldisulfonic acid, 1-naphthol-4-sulfonic acid, 2-naphthol-6-sulfonic acid, 2-naphthol-7-sulfonic acid, 1-naphthol-6-sulfonic acid, 2-naphthol-8-sulfonic acid, 4-aminonaphthalenesulfonic acid, and sulfanilic acid; The hydroxyphenol compound is at least one selected from the group consisting of bisphenol A, 4,4-biphenol, 3,3,5,5-tetramethyl-4,4-biphenol, bis(4-hydroxy-3,5-dimethylphenyl)methane, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 1,1-bis(2-naphthol), 4,4'-dihydroxydiphenyl sulfone, 2,4'-dihydroxydiphenyl sulfone, bis(4-hydroxy-3,5-dimethylphenyl)sulfone, 1,1,1-tris(4-hydroxyphenyl)methane, and 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane.
2. 2. The dispersion liquid for a solar cell electrode according to claim 1, wherein in the condensate (B), a molar ratio of an aromatic sulfonic acid compound monomer unit derived from a hydroxyphenol compound to an aromatic sulfonic acid compound monomer unit derived from a hydroxyphenol compound (hydroxyphenol compound monomer unit / aromatic sulfonic acid compound monomer unit) is 1 / 9 or more and 9 / 1 or less.
3. 3. The dispersion liquid for a solar cell electrode according to claim 1, wherein the condensate (B) has a weight average molecular weight (in terms of standard polyethylene glycol) of 500 or more and 100,000 or less.
4. The dispersion for a solar cell electrode according to any one of claims 1 to 3, wherein the condensate (B) is a resol type.
5. The dispersion for a solar cell electrode according to any one of claims 1 to 4, wherein the carbon material (A) is a fibrous carbon nanostructure.
6. 6. The dispersion for a solar cell electrode according to claim 1, wherein the solvent (C) contains water, and the pH of the dispersion is less than 7.
7. 7. The dispersion liquid for a solar cell electrode according to claim 1, comprising 50 parts by mass or more and 500 parts by mass or less of the condensate (B) per 100 parts by mass of the carbon material (A).
8. A conductive film for a solar cell electrode obtained by using the dispersion liquid for a solar cell electrode according to any one of claims 1 to 7.
9. A solar cell electrode comprising the conductive film for a solar cell electrode according to claim 8 .
10. A solar cell comprising the solar cell electrode according to claim 9 .
11. A step (1) of applying the dispersion liquid for a solar cell electrode according to any one of claims 1 to 7 onto a substrate and drying the dispersion liquid to form a conductive film; a step (2) of washing the conductive film obtained in the step (1) with a solvent to remove at least a part of the condensate (B) from the conductive film; The method for producing a conductive film for a solar cell electrode comprises the steps of:
Citation Information
Patent Citations
Carbon nano-tube fiber cement-based material and preparation thereof
CN101274831A
Piezoresistance / piezoelectric composite material, manufacturing method of material, sensor utilizing material and manufacturing method of sensor
CN102924020A
Transparent conductive film, and manufacturing method thereof
JP2009163959A
Carbon nanotube dispersion
JP2013199419A
Phenolic resin, electrode, lead storage battery and method of producing the same, and resin composition
JP2017160326A
